2007
DOI: 10.1016/j.juro.2006.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Over Expression of Stem Cell Homing Cytokines in Urogenital Organs Following Vaginal Distention

Abstract: Monocyte chemotactic protein-3 is significantly over expressed in rat urethral and vaginal tissues immediately following vaginal distention with above normal but decreasing expression 24 hours later. The association between monocyte chemotactic protein-3 over expression and targeted stem cell migration is under investigation. Successful characterization and control of such a repair mechanism in the lower urinary tract would introduce the potential for novel nonoperative treatments and/or preventive measures fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 19 publications
7
57
1
Order By: Relevance
“…9,15 Our findings confirm our previously reported observations showing increased expression of MCP-3 in the urethra immediately after VD. 4 However, we did not confirm the prior observation of SDF-1 downregulation after VD. This may be due, in part, because we did not include unanesthetized control or sham groups, since Woo et al found that MCP-3 expression was significantly increased 20-fold in both shams and controls.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…9,15 Our findings confirm our previously reported observations showing increased expression of MCP-3 in the urethra immediately after VD. 4 However, we did not confirm the prior observation of SDF-1 downregulation after VD. This may be due, in part, because we did not include unanesthetized control or sham groups, since Woo et al found that MCP-3 expression was significantly increased 20-fold in both shams and controls.…”
Section: Discussioncontrasting
confidence: 90%
“…This may be due, in part, because we did not include unanesthetized control or sham groups, since Woo et al found that MCP-3 expression was significantly increased 20-fold in both shams and controls. 4 We observed a significant trend in MCP-3 expression in rectal tissue after VD of increasing durations, suggesting that stem cell homing could play a role in rectal healing after delivery, a risk factor for fecal incontinence. 16 These findings could therefore indicate that treatments or preventatives based on facilitating stem cell homing may be applicable to fecal incontinence as well as SUI.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A higher prevalence or incidence of SUI has been observed in women who had at least one vaginal delivery than in women who underwent cesarean delivery [13][14][15][16][17][18]. There is 20-fold over expression of macrophage chemoattractant protein 3 in the urethra immediately following vaginal delivery, which has been postulated to be secondary to a shear effect on the pelvic muscles [19]. Vaginal delivery has been correlated with SUI development, likely via injury of the pelvic floor structures: muscles, nerves, organs, and extracellular matrix (ECM) responsible for continence [20].…”
Section: Neuromuscularmentioning
confidence: 99%